Health and safety reporting in New Zealand: How senior leaders are (slowly) moving away from TRIFR and lag indicators - Barton, Francois (New Zealand Journal of Health and Safety Practice, 2025)
In a world of acronyms, health and safety is not immune – LTIs, RAMs, ISO, IOSH, SoPs, HSNO – the list could continue. Perhaps the one referred to most frequently by Boards and Executives is TRIFR – total recordable injury frequency rates. It’s a measurement tool which has its place, but there is a growing view among many in health and safety that TRIFR alone as a lag indicator is not sufficient for Officers to take an informed view of health and safety performance across a business or operation. It’s for this reason that in early 2024 the Business Leaders’ Health and Safety Forum (Forum), a membership group of 400+ CEOs focused on improving health and safety leadership, officially paused its annual benchmarking project. This project, run for more than a decade saw participating organisations who belong to the Forum submit their annual TRIFR data, enabling them to compare their organisation’s performance against those in the same industry. For some members this was a key benefit of joining the Forum.